Influence of Vehicle Load as Point Load on Geogrid Deformation as Embankment Reinforcement on Soft Soil - A. Adhe Noor Patria SH (Dinamika Rekayasa, 2012)
Public contructions built on soft soil such as clay would face some problems such as long period consolidation time, unstability embankment slope, not easily compacted and high level settlement. Some solution that could be suggested were the usage of vertical drain, or the usage of geosynthetics material such as geogrid combined with floating piles. Analysis was carried out by using plaxis version 7.2. soil for embankment and embankment foundation was modelled in plane strain. Also geogrid and floating piles were modelled in plane strain too. Point load on top of embanknet were variated, they were 20, 40 and 60 kN/m. The simulation was carried out in staged contruction mode. The implementation of vehicle load increased geogrid deformation. It appeared as geogrid vertical displacement when the biggest vehicle load ( 60 kn/m) applied. In long term loading condition where excess pore water pressure was very small, vertical displacement of geogrid was – 0,5062 m for rigid embankment and – 0,6568 m for interface embankment. The difference occured due to slip at the interface of geogrid and soil. It leaded to adding soil mass supported by geogrid, furthermore the deflection of geogrid became bigger.